Analysis of influencing factor in students' selection of university based on DEMATEL method / Muhammad lzzat Azri Hassan ... [et al.] - Azri Hassan, Muhammad lzzat; Rupiwin, Munir Zaki; Mohd Nazley, Muhammad Syafiq; Md Rodzi, Zahari (UiTM Cawangan Negeri Sembilan, 2021)
A student's choice of university is one of the most crucial life choices they will make. With an ever-growing assortment of educational opportunities, prospective students seek universities that will give them an unforgettable educational experience. Additionally, students desire an educational programme that would prepare them for a great future and provide a profitable job for them. Therefore, this study conducts a decision making trial and evaluation laboratory (DEMATEL) analysis of the factors that influence students' university choices. Seven criteria were established in light of the recognised variables for university admissions. To gather data and information, questionnaires on the variables influencing university selection were distributed to UiTM Seremban students using Google Form platform. Data collection was done in one month and 123 respondents were obtained.